American sexual histories - Reis, Elizabeth, 1958- (Chichester, West Sussex : Wiley-Blackwell, 2012)
'The second edition of American Sexual Histories features an updated collection of sixteen articles by prominent historians and their corresponding primary sources that investigate issues related to human sexuality in America from the colonial era to the present day. Reflecting the myriad ways historians interpret and analyze sexuality and sexual trends, the essays offer in-depth exploration of topics such as contraception, prostitution, interracial relationships, same-sex desire, reproductive politics, and intersex and transgender history. Taken as a whole, the essays richly illustrate how the evolution of sexuality in America is a product of an ongoing negotiation of moral values and shifting political and economic circumstances. The chapters are arranged chronologically and include introductions by editor Elizabeth Reis which lend clarity and add historical context to the major articles and the supporting documents that follow. The carefully selected couplings of essays and primary sources allow readers to evaluate historical documents for themselves, test the interpretations of historians, and draw independent conclusions. Both scholarly and highly accessible, American Sexual Histories offers illuminating insights into the complex evolution of sex and sexuality in America.'--
Includes bibliographical references and index.
Keywords: Sex customs -- United States -- History; Sex customs -- United States -- History -- Sources